Do fluctuations in training load lead to changes in heart-rate variability in elite rugby union players? - Beck, R. (2018)
Theauthor is currently studying for a Masters in Strength & Conditioning from St Mary`s University, Twickenham. Over recent months he has been completing his dissertation, which used ithlete to monitor HRV. This is the final blog post in a three part series focusing on the results.